Reshaping Rural Economy through Integrative Leadership in Mining to Tourism Transition in Belitung, Indonesia - Arlina Arifin Djemahir; Rudy Pramono; Hendrawan Supratikno (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The economic transformation from extractive industries to tourism presents complex challenges for post-mining regions, requiring leadership that is visionary, collaborative, adaptive, and rooted in local values. This research examines integrative leadership's role in facilitating economic transition from tin mining to sustainable community-based tourism in Belitung Regency, Indonesia. Using qualitative multi-case methodology across nine villages with diverse socio-economic and geographic contexts, data were collected through in-depth interviews, participatory observation, focus group discussions, and document analysis. Thematic analysis supported by triangulation, member checking, and audit trails revealed that integrative leadership plays crucial roles in shaping collective visions, strengthening local institutions, and mobilizing community participation. Local leaders employed educational, participatory, and collaborative strategies addressing key challenges including social resistance, limited human capital, and mining legacy dependency. The transformation yielded increased household income, economic diversification, and cultural identity revitalization, though impacts varied significantly across villages. Tourism sustainability in these post-mining communities depends critically on leadership quality, institutional capacity, and ecological awareness. This study contributes to integrative leadership theory development within post-extractive economic contexts and offers practical insights for policymakers and stakeholders promoting inclusive sustainable tourism transitions.